GROUND IMPROVEMENT TEST CHEMICAL PROPERTIES OF GOLD MINE USED BY USING SOME KIND OF COMPOST - Frengky F. Kosho; Zetly Tamod; Jenny Rondonuwu; Wiesje Kumolontang (COCOS, 2013)
ABSTRACT The purpose of this study was to determine the effect of compost on land mined gold and knowing which one is the best type of compost to the early growth of the plant jackfruit. This research used Completely Randomized Design (CRD) factorial with 2 faktoral namely Factor A: types of compost with three levels while the B factors and three levels of fertilization and repeated 3 times so have 27 pot experiment. The results composting on mined land can improve soil chemical properties in this case the addition of the nutrients N, P, K and C-organic. Nutrient content of compost can be seen that the highest N content contained in compostable materials made of peanuts is 0.8%. While the highest available P in compost bins gamal is 16.79 ppm, the highest available K in compost market is 55.3 ppm and C-gamal organic compost is the highest at 9.11%. Jackfruit plant growth height and number of leaves both the best in the mined soil compost bins given market.